ANALISIS PENGARUH KUALITAS PRODUK, HARGA, DAN KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN (STUDI KASUS PADA DISTRO NUMERIQUE DI KOTA PONTIANAK) - B31190986, SILVESTER TONI SETIAWAN (Jurnal Manajemen Update, 2016)
This study aims to determine the effect of product quality, price, and service quality on customer loyalty in Distro Numerique Pontianak. Where the independent variables consisting of product quality, price, and service quality affects customer loyalty as the dependent variable. This research was conducted in Distro Numerique Pontianak. Methods of data collection in this study is a questionnaire filled out by the respondent that the Distro Numerique consumers who have shopped at least twice. To analyse the data, writer using SPSS 16 version. Results of analysis using multiple linear regression can be seen that the variable quality of the products have a significant effect on customer loyalty Distro Numerique. Second, the price variable has no significant effect on customer loyalty Numerique distributions. Third, service quality has positive influence on customer loyalty Distro Numerique. Results of analysis using test f knowable product quality, price, and quality of service can be used to measure customer loyalty Distro Numerique. Results of analysis using the coefficient of determination is known that 15.9% variable customer loyalty can be explained by variation of the variable product quality, price, and quality of service, while the rest is explained by other variables that are not included in this study. Keywords: product quality, price, service quality, customer loyalty. Â